High particulate organic carbon export during the decline of a vast diatom bloom in the Atlantic sector of the Southern Ocean. (April 2017) - Roca-Martí, Montserrat; Puigcorbé, Viena; Iversen, Morten H.; van der Loeff, Michiel Rutgers; Klaas, Christine; Cheah, Wee; Bracher, Astrid; Masqué, Pere
Abstract: Carbon fixation by phytoplankton plays a key role in the uptake of atmospheric CO2 in the Southern Ocean. Yet, it still remains unclear how efficiently the particulate organic carbon (POC) is exported and transferred from ocean surface waters to depth during phytoplankton blooms. In addition, little is known about the processes that control the flux attenuation within the upper twilight zone. Here, we present results of downward POC and particulate organic nitrogen fluxes during the decline of a vast diatom bloom in the Atlantic sector of the Southern Ocean in summer 2012. We used thorium-234 ( 234 Th) as a particle tracer in combination with drifting sediment traps (ST). Their simultaneous use evidenced a sustained high export rate of 234 Th at 100 m depth in the weeks prior to and during the sampling period. The entire study area, of approximately 8000 km 2, showed similar vertical export fluxes in spite of the heterogeneity in phytoplankton standing stocks and productivity, indicating a decoupling between production and export. The POC fluxes at 100 m were high, averaging 26±15 mmol C m −2  d −1, although the strength of the biological pump was generally low. Only <20% of the daily primary production reached 100 m, presumably due to an active recycling of carbon and nutrients. Pigment analyses indicated that direct sinking of diatoms likely caused the high POC transfer efficiencies (~60%) observed between 100 and 300 m, although faecal pellets and transport of POC linked to zooplankton vertical migration might have also contributed to downward fluxes.